The Relationship Between Work-Life Balance and Employee Performance in Employees of PT Milion Limbah Ambon - Juangericke Loupatty; Maria Prima Novita (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aims to analyze the relationship between work-life balance and employee performance at PT Milion Limbah Ambon, a plastic waste treatment company located in Ambon. This relationship has not been previously investigated at this company. Furthermore, this research contributes valuable data to the literature by focusing on a region outside Java, as most comparable studies are Java-centric. This study comprised 66 employees of PT Milion Limbah Ambon as the total sample, with most respondents residing in areas close to the company. Data were collected through an online questionnaire using the Individual Work Performance Questionnaire (IWPQ) scale and the work-life balance scale. Results showed a positive and significant relationship (r = 0.903) between work-life balance and employee performance, indicating that improving work-life balance can significantly increase employee performance. These findings provide a basis for formulating work flexibility policies or time-management training to increase productivity. Keywords: work-life balance, employee performance, industrial and organizational psychology